Women Crafting New Work: The Learning of Women Entrepreneurs - Tara Fenwick; Susan Hutton (Adult Education Research Conference, 2000)
This report presents findings of a cross-Canada qualitative study examining learning processes of new women business-owners, to explore the emergence and nature of women’s experiential or ‘informal’ learning in work they invent.